PENGARUH TRANSFORMASI DIGITAL DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA DINAS KETAHANAN PANGAN, PERTANIAN DAN PERIKANAN KOTA PROBOLINGGO - Eko, Muhammad; Kumala Devi, Nourma Ulva; Nurany, Fierda (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2025)
This study was conducted to determine the effect of digital transformation and service quality on community satisfaction at the Probolinggo City Food Security, Agriculture and Fisheries Service. This research method uses quantitative research. The population in this study is the community around the probolinggo city food security, agriculture and fisheries office using a saturated sample technique of 60 respondents. The data sources used are primary data and secondary data. The data was collected using the distribution of questionnaires which were managed with validity tests, reliability tests, classical assumption tests, multiple linear regression tests and t tests. where it was found that digital transformation and service quality had an effect on community satisfaction. Through the results of the calculation of the digital transformation variable that has been carried out, it is obtained tcount> ttable or 2.214> 1.673 with a sig value of 0.031 <0.05, meaning that the digital transformation variable has an effect on community satisfaction at the Food Security, Agriculture and Fisheries Office of Probolinggo City. While the results of the calculation of the service quality variable obtained tcount> ttable or 8.594> 1.673 with a sig value of 0.000 <0.05, meaning that the service quality variable has an effect on community satisfaction at the Food Security, Agriculture and Fisheries Service of Probolinggo City. Thus it is hoped that the Probolingo City Food Security, Agriculture and Fisheries Service will maintain service quality and continue to update digital transformation by presenting features that can facilitate community access. Keywords: digital transformation, service quality and community satisfaction.